Alguns aspectos problemáticos relacionados ao ensino-aprendizagem da álgebra linear - COIMBRA, Jarbas Lima (2008)
This study deals with some aspects that I consider as possible difficults to the Linear Álgebra lessons understanding. It treats of a subject of huge importance for many graduation university courses and I consider that any study that intends to improve this teaching is essencial. It contains innumerous considerations about difficults that students can face during the subject learning, like those related to the knowledge brought from the high school, witch can either be used as a help as can cause understanding troubles of general lesson concepts, difficulties with use of geometry, difficulties with expressions known from other classes, logical difficulties, and others difficulties.